A survey to evaluate the efficacy of virechana, basti and knee dhara in patients with Osteoarthritis of knee joint - Naram, Smita P.; Parekh, Hemang; Mahajan, Deepak S.; Naik, Ronak D. (International Journal of Research in Medical Sciences, 2019)
Background: The objective of this study was to evaluate the role of Virechana (Arhtrox) followed by Kalbasti (14 in number), Knee dhara and Matrabastiin knee osteoarthritis patients. Methods: From OPD of Ayushakti Ayurveda Pvt. Ltd., 60 Patients suffering from knee Osteoarthritis (Janusandhigatavata) were selected randomly as per the inclusion and exclusion criteria. On the basis of specific criteria prepared. Group-I-(30 patients) received only Ayushakti herbs for Osteoarthritis, viz. Painmuktimj, Painmukti sandhical and Painmukti cream for LA Group-II-(30 patients) received Virechana (Arthrox), KalBastikrama (14 Bastis) and Knee dhara with oil followed by Matrabasti (60 ml) twice a week for 6 months along with Ayushakti herbs for Osteoarthritis. Each participant was in the study for 6 months. The entire study duration was 12 months. Result: About 87 patients were enrolled in the study of which 60 completed the study, 27 patients were drop out of the study, at the different stages of project mainly due to poor follow up. Significant reduction in pain was observed in Groups I and II as compared to the baseline (p <0.001) Pain scale (p <0.001). Conclusion: In this study, good relief was offered in knee joint pain, stiffness and mobility, and daily activities like standing, walking, and climbing. Painmukti mj, Painmukti cream and Painmukti Sandhical tablets are Anti-inflammatory, Analgesic but their efficacy can be increased with Virechana.